(untitled) (GYMNASIUM, 2017)
There are a multitude of factors that may influence the efficiency of a junior football player towards the end of a match; a technical error, a deficient physical condition or a lack of concentration, which lead in most cases to the loss of the match or points. Coaches from various junior teams and even senior teams, so as to motivate the negative result, explain the failures or the lack of efficiency of a player or of the teams they run by using the sentence, ”in decisive moments of the match my players have given proof of lack of concentration". In this respect, in order to find the determining factor, we have to do a thorough analysis on the management of the last minutes of a football match, so that we can identify and fight its negative effects in the future.